Continuous Improvement According to the Japanese Kaizen Approach for Developing University Performance - Madhloom Al-Enizi, Kassim Mohammed (ExcelingTech, 2020)
Abstract The current research aims to identify the theoretical foundations of the Kaizen approach in continuous improvement as an administrative philosophy that the administration can adopt in academic education organizations represented by universities, and then apply the kaizen requirements to improve and develop the performance of university organizations. The descriptive and analytical approach was used in the research, and the research reached that the application of continuous improvement requirements serves the educational process and the process of continuous improvement for students of the level of competence of higher education outputs, an understanding of the organizational objectives, as well as the participation and support of the administration, and the participation of all individuals working in the process of continuous improvement of their activities..